Pengaruh Live Streaming Commerce dan Online Customer Review Terhadap Purchase Decision Melalui Trust Sebagai Variabel Mediasi Pada E-Marketplace Shopee (Studi Pada Produk Perawatan Bayi) - Jumai Latte; Fatimah (Program Magister Ilmu Administrasi Bisnis FISIP Universitas Lambung Mangkurat, 2025)
Abstract: This study analyzes the influence of Live Streaming Commerce and Online Customer Review on Purchase Decision, with Trust as a mediating variable in baby care products on the Shopee e-marketplace. Using a quantitative explanatory approach and survey method, data were collected from 170 Shopee users who had watched live streaming sessions and read customer reviews. The data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) through SmartPLS 4.0. The results show that Live Streaming Commerce has a positive and significant effect on both Trust and Purchase Decision, while Online Customer Review does not significantly affect either variable. Trust has the most dominant and significant influence on Purchase Decision and strengthens the relationship between live streaming activity and purchase behavior. These findings indicate that consumer trust is the main factor driving purchase decisions and enhancing the effectiveness of digital marketing strategies on Shopee